2018
DOI: 10.21147/j.issn.1000-9604.2018.04.06
|View full text |Cite
|
Sign up to set email alerts
|

A radiomic nomogram based on an apparent diffusion coefficient map for differential diagnosis of suspicious breast findings

Abstract: ObjectiveTo develop and validate a radiomic nomogram based on an apparent diffusion coefficient (ADC) map for differentiating benign and malignant lesions in suspicious breast findings classified as Breast Imaging Reporting and Data System (BI-RADS) category 4 on breast magnetic resonance imaging (MRI).MethodsEighty-eight patients diagnosed with BI-RADS 4 findings on breast MRI in the First Affiliated Hospital of China Medical University from December 2014 to December 2015 were retrospectively analyzed in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…Other than DCE‐MRI, MR sequences such as nonenhanced T 1 ‐weighted images, diffusion‐weighted images, and T 2 ‐weighted images have been used to improve lesion characterization. Investigators have also developed multiparametric models combining diffusion‐weighted imaging with DCE‐MR for lesion discrimination, with accuracies up to 0.93. Specific features that were significantly different between benign and malignant lesions included entropy and signal enhancement ratio .…”
Section: Lesion Classificationmentioning
confidence: 99%
“…Other than DCE‐MRI, MR sequences such as nonenhanced T 1 ‐weighted images, diffusion‐weighted images, and T 2 ‐weighted images have been used to improve lesion characterization. Investigators have also developed multiparametric models combining diffusion‐weighted imaging with DCE‐MR for lesion discrimination, with accuracies up to 0.93. Specific features that were significantly different between benign and malignant lesions included entropy and signal enhancement ratio .…”
Section: Lesion Classificationmentioning
confidence: 99%
“…Since BI-RADS 5 lesions have typical signs of malignancy, and almost all lesions are malignant (>95% risk of malignancy), the inclusion of BI-RADS 5 lesions may improve the prediction performance of the radiomic nomogram to some extent. Similarly, Hu et al [ 15 ] developed and validated an MRI radiomic nomogram for differentiating benign and malignant BI-RADS 4 lesions with an AUC of 0.79 in the testing set, which was significantly lower than that of our ABVS radiomic nomogram (AUC, 0.925), and the possible reasons are as follow. First, we included a larger sample size of BI-RADS 4 lesions (223 vs. 86), which may be the main reason.…”
Section: Discussionmentioning
confidence: 89%
“…It can extract high-throughput quantitative features that may not be observed directly by the naked eye from single or multiple medical images, and subsequently combine these features with clinical information to improve disease diagnosis and prognostic evaluation [ 11 ]. A large number of studies have reported the application of radiomic nomograms based on various imaging modalities, such as computed tomography (CT), magnetic resonance imaging (MRI), positron emission tomography-computed tomography (PET-CT), and US, which have showed great potential in the classification and prediction of breast cancer [ 12 , 13 , 14 , 15 , 16 ]. However, only a few studies have focused on BI-RADS 4 lesions [ 15 , 16 ], and no studies have been based on automatic breast volume scanner (ABVS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiomics can be combined with the imaging appearance to further improve the differential diagnosis ability of the lesion (30,31). The AK, an imaging analytic software used in this study, has been used in many research reports (32,33). A previous study showed that radiomic feature-based CT imaging signatures allow the prediction of lymph node metastasis in cancer and could facilitate the preoperative individualized prediction of lymph node status (20).…”
Section: Discussionmentioning
confidence: 99%